Scientific Opinion on the safety evaluation of the process “Holfeld Diamat” used to recycle post-consumer PET into food contact materials - EFSA Panel on Food Contact Materials, Enzymes, Flavourings and Processing Aids (CEF) (EFSA Journal, 2013)
This scientific opinion of the EFSA Panel on Food Contact Materials, Enzymes, Flavourings and Processing Aids deals with the safety evaluation of the recycling process Holfeld Diamat (EC register number RECYC076) which is based on the Diamat ® technology. The input of the process is washed and dried PET flakes originating from collected post-consumer PET containers, mainly bottles, containing no more than 5 % of PET from non-food consumer applications. Through this process, post-consumer washed and dried PET flakes are mixed up to 50 % with virgin PET flakes before being heated in a crystallisation reactor (step 2) and extruded under vacuum into sheets (step 3). After having examined the challenge tests provided, the Panel concluded that the decontamination in the two consecutive extruders step 3 is the critical step for the decontamination efficiency of the process. The operating parameters to control its performance are well defined and are the temperature, the pressure and the residence time. The operating parameters of these steps in the process are at least as severe as those obtained from the challenge test. Under these conditions, it was demonstrated that the recycling process is able to ensure that the level of migration of potential unknown contaminants into food is below a conservatively modelled migration of 0.15 μg/kg food derived from the exposure scenario for toddlers. Therefore, the recycled PET obtained from the process Holfeld Diamat intended for the manufacture of recycled thermoformed trays and containers made with up to 50 % recycled post-consumer PET and intended for contact for long term storage at room temperature with all types of foodstuffs except packaged water is not considered of safety concern.